Recuperación y transferencia de embriones de vacas Holstein de élite con infecciones uterinas recurrentes (1998)
ABSTRACT: Six high quality Holstein cows (average of 6049 kg/305 days milk yield; 9.6 years old with 7.8 calving; 13.2 months of calving interval; and 1.9 breeds/conception) presented recurrent uterine infections with 340.5 open days after calving. After the last successful uterine treatment cows were induced to superovulation with constant FSH doses (days 11-14 of cycle), PGF2α day 13 (AM:PM) with AI (AM:PM) and GnRH treatment (AM) at the PGF2α-induced estrus. Eight days after AI cows were flushed and embryos recovered, classified and transferred to Holstein or cross-breed (F1) Brahman heifers synchronized with the donor. The average recovery rate was 10.3 embryos/flushing, with 39.4% non-fertilized oocytes, 30.3% attached and embryo quality significantly correlates with implantation rate (p <0.05). The age of the cows was significantly associated with embryo-recovering rate (p < 0.05). These results showed that progeny from high-quality dairy cows with recurrent uterine infections can be recovered by embryo transfer.